Transition and Transformation Victor Sjöström in Hollywood 1923-1930 - Florin, Bo (Film Culture in Transition, 2012)
In 1923, Victor Sjöström (1879-1960) got an offer from Goldwyn Pictures to come to Hollywood. This was nothing unusual for a successful European director: - Metro's bring - ing them in by car load - , as Photoplay stated in 1926. At the time, Sjöström was Sweden's most renowned director, who had become world famous for his austere and naturalistic film style. Sjöström stayed in Hollywood for seven years and made nine films. What happened during those years to the characteristic style that he had developed in Sweden? How was it transformed by Hollywood? Did he maintain any of his stylistic particularities from the Swedish period? How were his Hollywood films received by the American and Swedish critics? This portrayal of a European in Hollywood reveals how Sjöström, in adapting to the new production system, integrated and developed various stylistic elements from the Swedish years in a radically different context. Transition and Transformation is the first book-length study dedicated to the films of Victor Sjöström made in Hollywood, which also nuances the picture of the American production system.